Gaming and religion: the impact of spirituality and denomination - Braun, Birgit; Kornhuber, Johannes; Lenz, Bernd (Journal of religion and health, 2016)
A previous investigation from Korea indicated that religion might modulate gaming behavior (Kim and Kim in J Korean Acad Nurs 40:378-388, 2010). Our present study aimed to investigate whether a belief in God, practicing religious behavior and religious denomination affected gaming behavior. Data were derived from a Western cohort of young men (Cohort Study on Substance Use Risk Factors, n = 5990). The results showed that a stronger belief in God was associated with lower gaming frequency and smaller game addiction scale scores. In addition, practicing religiosity was related to less frequent online and offline gaming. Finally, Christians gamed less frequently and had lower game addiction scale scores than subjects without religious denomination. In the future, these results could prove useful in developing preventive and therapeutic strategies for the Internet gaming disorder.
Online veröffentlicht: 21. November 2015